Unofficial Payments for Acute State Hospital Care In Kazakhstan. A Model of Physician Behaviour with Price Discrimination and Vertical Service Differentiation - Robin Thompson; Ana Xavier (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
In most of the countries in transition from a planned to a market economy (firmer Soviet Union (FSU) and Central and Eastern Europe (CEE)) patients are routinely asked to pay unofficially for the medicines and other supplies that ought to be free. They are often described as 'payments to individuals or institutions in cash or in kind made outside official payment channels for services that are meant to be covered by the public health care system? Despite their illegality, surveys undertaken in Bulgaria, Poland, Turkmenistan, and Tajikistan found that 43%, 46%, 50%, and 70% of the patients paid for officially free services. We consider a simple model of discriminatory pricing and service differentiation in which state salaried physicians employed in a monopoly state acute hospital adjust the quality of care to the level of unofficial payment paid by the patient. On one hand, low motivated and poorly paid physicians exploit their monopoly position by choosing the payment / quality combination to be provided with the knowledge that corruption is largely ignored. There is a cost involved in the provision of each type of treatment (e.g. the potential fine imposed if found). On the other hand, the general quality of the health care provided by the sate is perceived to be poor and some patients are willing to pay unofficially in an attempt to improve the quality of care in some way. Patients have heterogeneous preferences for care quality. Physicians exploit their position as providers and the demand for quality, and offer differing levels of care quality to paying and non-paying patients. This behavioural model is then tested using a unique dataset obtained from a survey of 1508 discharged hospital surgical and trauma patients treated in three hospitals in Almaty City, Kazakhstan in 1999. Data include infirmation on patients?experience in hospital including where and how much was paid unofficially and patients'socio-economic characteristics. Each patient is identified by an ICD10 code and most surgical and trauma conditions for which entitlement is free are represented. We use waiting time for admissions and hospital length of stay (LOS) as observable measures of quality. Process indicators, such as 'time?have traditionally been used to monitor hospital perfirmance. Waiting is used as a quality proxy in studies of health service demand and surveys suggest that patients pay to reduce the wait. LOS is taken as a measure of quality in that it is detfirmined by physicians and may proxy not only more attention paid to the patient by the doctor but also fewer post-surgical complications in a context where post-hospital follow up is very limited. We then compare these results with those using a categorically (ordered) variable reflecting the subjective view of the patients towards the health care quality received. We use both OLS analysis and, in the case of the categorical variable, ordered probit models to test whether, as suggested by the theory, surveys and anedoctal reports, patients are paying for increased treatment quality. We account for heteroskedasticity, potential endogeneity, and test the general model specification. We look at both pooled and unpooled hospital data. We find that: patients are paying to decrease the time for surgical admissions; patients are paying to stay longer in hospital (or more realistically not to discharged early); there is some patient heterogeneity. These results confirm to the theoretical modelling and the anedoctal reports suggesting that patients are paying for quality and physicians are exploiting their monopoly power to charge infirmal payments, which result in an increase in their incomes. This paper contributes to the literature in various ways: a) as one of the first attempts to use economic theory to model unofficial payments and related physician behaviour; b) we use original data from Kazakhstan to conduct econometric analysis so as to explore whether prior payment influences the quality of care received (measured using process indicators) while previous studies were limited to answer the who, how much, when and to whom; c) the unofficial pricing behaviour of state salaried physicians in a public sector hospital may offer insights into the general behaviour of physicians.
Keywords: I1; P3; 330; transition economies; unofficial or informal payments for health care; length of stay; ordered probit and marginal effects; Krankenhausfinanzierung; Korruption; Ärzte; Preisdifferenzierung; Kasachstan; Patienten